PROSES KREATIF "THE BEAUTY OF ASIA" DAN INTEGRASINYA DALAM MANAJEMEN PEMASARAN KOTA SEMARANG : Tinjauan Terhadap Bran Kota Semarang - Nurhayati, Eny Farida (VITASPHERE, 2012)
Implementati~n of Indonesia aoutonomy act brings arising of competition among Indonesian cities and towns to attract investors, interest of city population, as well as tourists. Cities/ towns compete to create city/town brand, so the essence of cities/towns is actually competition of citie/town brands. Since 2006 the "Beauty of Asia" became the brand of Semarang city. Pro-contra to its sudden appearance indicates dissatisfaction among the society because they have not been involved in the creative process. Counter-productive may arise from unaware community as well as its un-integration in city development programmed. This can lead to failure in competition with other cities and achievement of its ultimate goals. This paper reviews some scientific literatures to illustrate the process of city branding and how the brand as a marketing communication tool is integrated to city development programmed.